PEMBUATAN SENSOR GAS H2S BERBASIS POLYANILINE FIELD EFFECT TRANSISTOR (PFETs) DENGAN METODE CASTING - Taofik Jasa Lesmana (Jurnal Biofisika, 2012)
H2S  gas  sensor  has  been  made  based  on  Field  Effect  Transistors  (FETs)  with polyaniline  (PANI)  as the  active  layer of  the sensor.  PANI  layer  was grown  on top of a dielectric material  (SiO2)  with a  casting  method.  Optical  properties of  the dielectric layer  tested  to  see  present  layers  as  one  constituent  sensor.  Sensor  electrically tested  to  see  the  effect  of  terrain  characteristics  and  sensitivity  to  H2S  gas.  Drain current  increases  with  increasing  negative  gate  voltage.  The  interaction  of  sensor with  the  H2S  is  indicated  by  the  increasing  drain  current  when  increased concentrations of H2S gas.